The impact of HIV on children's welfare - Kenneth Harttgen (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2007)
Children living in HIV/AIDS affected households bear the heaviest burden of the epidemic. Besides direct vertical transmission, HIV/ AIDS potentially worsens the children's welfare indirectly through its socio-economic impact. This paper uses household survey data including information about individual HIV infection status to analyze the direct and indirect effects of HIV-infected household members on child mortality, undernutrition and educational attainment for Burkina Faso, Cameroon, Ghana and Kenya. The results indicate that the main channel through which HIV effects the child mortality risk is mother to child transmission. Whereas no effect of HIV is found on child mortality and undernutrition, a negative effect for school enrollment is found for Burkina Faso and Cameroon.
Keywords: I12; I30; I31; J13; R20; 330; AIDS; Kindersterblichkeit; Unterernährung; Bildungschancen; Kinder; Afrika südlich der Sahara